PENGARUH PENGETAHUAN, REPUTASI, LINGKUNGAN DAN RELIGIUSITAS TERHADAP MINAT PELAJAR SEKOLAH MENENGAH KEJURUAN PRODI PERBANKAN SYARIAH DALAM MENABUNG DI BANK SYARIAH - Fajar Mujaddid; Pandu Tezar Adi Nugroho (Universitas Muhammadiyah Prof Dr Hamka, 2019)
This paper examines the factors affecting Vocational High School students majoring Islamic banking who were interested in saving for Islamic banks. Based on the sample analysis, there were 72 respondents in VHS 20 Jakarta, VHS Al-Hasra Depok, and VHS Muhammadiyah 1 Ciputat. Using multiple linear regression analysis, this research shows 51,9 percent of the variable knowledge, reputation, environment, and religiosity define the interest of the student in saving. Meanwhile, the results of the analysis show the Reputation and Religiosity variables had a significance of 0.019 and 0.000, which means that the reputation and religiosity variables had an influence on the interest in the saving for students in Islamic banks. These findings can provide opportunities for Islamic banks to increase socialization to Muslim communities that do not yet know Islamic banks, one of them are by supporting Islamic activities such as ‘Islamic Forum' (Majelis Taklim) and educating religious teachers about Islamic banks in order to promote and campaign for savings in Islamic banks. Keywords: Saving Interest, VHS Students, Islamic Bank, Knowledge, Reputation, Environment, Religiosity, Multiple Linear Regression